Andrographolide suppresses RANKL-induced osteoclastogenesis in vitro and prevents inflammatory bone loss in vivo - Zhai, Z J (British Journal of Pharmacology, 2014)
BACKGROUND AND PURPOSE: Osteoclasts play a pivotal role in diseases such as osteoporosis, rheumatoid arthritis and tumour bone metastasis. Thus, searching for natural compounds that may suppress osteoclast formation and/or function is promising for the treatment of osteoclast-related diseases. Here, we examined changes in osteoclastogenesis and LPS-induced osteolysis in response to andrographolide (AP), a diterpenoid lactone isolated from the traditional Chinese and Indian medicinal plant Andrographis paniculata. EXPERIMENTAL APPROACH: Effects of AP on osteoclast differentiation and bone resorption were measured in vitro. Western blots and RT-PCR techniques were used to examine the underlying molecular mechanisms. The bone protective activity of AP in vivo was assessed in a mouse model of osteolysis. KEY RESULTS: AP concentration-dependently suppressed RANKL-mediated osteoclast differentiation and bone resorption in vitro and reduced the expression of osteoclast-specific markers, including tartrate-resistant acid phosphatase, calcitonin receptors and cathepsin K. Further molecular analysis revealed that AP impaired RANKL-induced NF-κB signalling by inhibiting the phosphorylation of TGF-β-activated kinase 1, suppressing the phosphorylation and degradation of IκBα, and subsequently preventing the nuclear translocation of the NF-κB p65 subunit. AP also inhibited the ERK/MAPK signalling pathway without affecting p38 or JNK signalling. CONCLUSIONS AND IMPLICATIONS: AP suppressed RANKL-induced osteoclastogenesis through attenuating NF-κB and ERK/MAPK signalling pathways in vitro, thus preventing bone loss in vivo. These data indicated that AP is a promising natural compound for the treatment of osteoclast-related bone diseases.